2014
DOI: 10.1136/bmjopen-2013-004166
|View full text |Cite
|
Sign up to set email alerts
|

Costs for collagenase injections compared with fasciectomy in the treatment of Dupuytren's contracture: a retrospective cohort study

Abstract: ObjectivesTo compare collagenase injections and surgery (fasciectomy) for Dupuytren's contracture (DC) regarding actual total direct treatment costs and short-term outcomes.DesignRetrospective cohort study.SettingOrthopaedic department of a regional hospital in Sweden.ParticipantsPatients aged 65 years or older with previously untreated DC of 30° or greater in the metacarpophalangeal (MCP) and/or proximal interphalangeal (PIP) joints of the small, ring or middle finger. The collagenase group comprised 16 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 17 publications
1
46
0
2
Order By: Relevance
“…19 In terms of overall cost, CCH injections were found to be just below $700 less expensive than fasciectomy. 2 This study had several limitations. The ability to query for procedures in the PearlDiver database is dependent on the availability of specific CPT codes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In terms of overall cost, CCH injections were found to be just below $700 less expensive than fasciectomy. 2 This study had several limitations. The ability to query for procedures in the PearlDiver database is dependent on the availability of specific CPT codes.…”
Section: Discussionmentioning
confidence: 99%
“…Although CCH costs greater than $3000 per injection, studies have demonstrated fewer follow-up and therapy visits required postprocedure and significantly less overall costs for patients receiving CCH injection as compared to fasciectomy. 2,6,15 Given the disparity in price between the 2 procedures, financial feasibility cannot be discounted as a possible factor involved in the decreasing percentage of patients receiving fasciectomy and the increasing rates of CCH injection. As CCH injections are more commercialized and marketed by the parent company toward individuals through various medias, the use can be expected to increase or at least discussed during clinic visits.…”
Section: Discussionmentioning
confidence: 99%
“…A Spanish study 20 including 91 patients found that CCH was associated with cost savings compared with fasciectomy, ranging from 29% to 51%. A Swedish hospital study 21 of 32 patients found that the total treatment cost for fasciectomy was $2,103, higher than the total treatment cost of CCH of $1,418. The drug cost for CCH was $970/ injection (in 2011e2012).…”
Section: Discussionmentioning
confidence: 96%
“…Bei einer Prävalenz von 0,6 bis 31,6 % in den westlichen Industrieländern [6], der sich daraus ableitenden sozioökonomischen Bedeutung der Dupuytren-Kontraktur sowie des Kostendrucks im Gesundheitswesen sind außer der medizinischen Bewertung neuer Behandlungsmethoden im Vergleich zum Goldstandard auch ökonomische Betrachtungen sinnvoll und notwendig. In den vergangenen 2 Jahren sind Kosteneffektivitätsanalysen aus verschiedenen westlichen Industrieländern publiziert worden [7][8][9][10][11] In der statistischen Analyse der Datensätze zeigten sich bei beiden Gruppen hinsichtlich der Altersverteilung (p = 0,097) sowie den präoperativen …”
Section: Einleitung ▼unclassified